2017
DOI: 10.3389/fpls.2017.01325
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetic Differentiation and Taxonomy of Three Closely Related Species of Saxifraga (Saxifragaceae) from Southern Tibet and the Hengduan Mountains

Abstract: The effects of rapid, recent uplift of the Hengduan Mountains on evolution and diversification of young floristic lineages still remain unclear. Here, we investigate diversification of three closely related Saxifraga species with a distribution restricted to the Hengduan Mountains (HM) and southern Tibet, and comment on their taxonomy based on molecular evidence. Three chloroplast DNA fragments (rbcL, trnL-F, trnS-G) and the nuclear ribosomal DNA internal transcribed spacer (ITS) were employed to study genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 79 publications
2
14
0
Order By: Relevance
“…Khakhlova et al (2006) suggested that gene divergence with less variability in the IR and coding regions may be a result of copy corrections during gene conversion, which can correct or delete the mutation. Codons were shown to have a strong tendency toward A or U at the third codon position, which is similar to the expression of an A/U ending in other plants (Gao et al, 2017;Clegg et al, 1994;Mader et al, 2018;Meng et al, 2018). This phenomenon may explain why the Adenine-Thymine (AT) content is slightly higher than the GC content in the cp genome of Dicliptera.…”
Section: Sequence Variation Among Five Dicliptera Speciessupporting
confidence: 62%
“…Khakhlova et al (2006) suggested that gene divergence with less variability in the IR and coding regions may be a result of copy corrections during gene conversion, which can correct or delete the mutation. Codons were shown to have a strong tendency toward A or U at the third codon position, which is similar to the expression of an A/U ending in other plants (Gao et al, 2017;Clegg et al, 1994;Mader et al, 2018;Meng et al, 2018). This phenomenon may explain why the Adenine-Thymine (AT) content is slightly higher than the GC content in the cp genome of Dicliptera.…”
Section: Sequence Variation Among Five Dicliptera Speciessupporting
confidence: 62%
“…Khakhlova & Bock (2006) suggested that gene divergence with less variability in the IR and coding regions may be a result of copy corrections during gene conversion, which can correct or delete the mutation. Codons were shown to have a strong tendency toward A or U at the third codon position, which is similar to the expression of an A/U ending in other plants (Gao et al, 2017;Clegg et al, 1994;Mader et al, 2018;Meng et al, 2018). This phenomenon may explain why the Adenine-Thymine (AT) content is slightly higher than the GC content in the cp genome of Dicliptera.…”
Section: Sequence Variation Among Five Dicliptera Speciesmentioning
confidence: 63%
“…Saxifraga L. is the largest genus of Saxifragaceae, consisting of 450-500 species in at least 13 sections (Tkach et al 2015;Ebersbach et al 2017a;Gao et al 2017;Li et al 2018). The most species-rich section of Saxifraga is 1 3…”
Section: Introductionmentioning
confidence: 99%